Business, politics, and the state in Africa : challenging the orthodoxies on growth and transformation - Kelsall, Tim, 1970-; Booth, David, 1945- (London ; New York : Zed Books, 2013)
Drawing on studies of Rwanda, Ethiopia, Tanzania and Ghana this book provides a new theory of the polticial and institutional conditions required for growth in Africa.
Includes bibliographical references (p. [167]-184) and index.
BIGD
Keywords: Economic development -- Africa; Africa -- Economic policy